The impact of company size and growth on the relationship between operating cash flow and change in dividends - Dr. Moamer Touzer Mouftah, (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2024)
This study aimed to find out the extent of the impact of company size and growth level on the relationship between operating cash flows and the change in dividends. The study population consisted of Jordanian companies listed on the Amman Stock Exchange during the study period, and to achieve the objectives of the study, a sample of 162 companies was selected, representing 62.5% of the study population. To test the hypotheses, the SPSS program was relied on and the appropriate statistical methods were used. The study found that there is impact of company size and growth level on the relationship between operating cash flow and the change in dividends.